PENDIDIKAN ABSTINENSI DALAM KURIKULUM PENDIDIKAN DASAR INDONESIA - Nurfadhilah (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
Abstinence education for young students has not been widely applied in Indonesia. Other countries conducted various implementation, all of them agreed the importance of reproduction health, sexuality, and population studies for the community, notably adolescent. The study aims to compare the application of abstinence education in some countries through literature review. As many as 31 articles regarding abstinence and abstinence education reviewed as well as core competences and basic competences in Curricullum-2013 for elementary education. Some of the articles claimed that abstinence-only education had nothing to do with the decrease of teenage/premarital pregnancy. Others proved that abstinence education with specific materials/topics relevant with culture and values have some effect on knowledge and responsible behaviour. However, parents and teachers still had many challenges and barriers in delivering the topics and using the media. Policy implementation urged and needed now are identification of education materials, the use of media, and development of teacher’s guide book.